Growth and Yield of Avicennia Officinalis (Baen) L. And Heritiera Fomes (Sundri) Buch. Ham. Plantations Established From Plus Tree Seeds in the Western Coastal Belt of Bangladesh - Miah, Md Abdul Quddus; Moula, Md Golam (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Abstract not available J. Asiat. Soc. Bangladesh, Sci. 46(2): 209-214, December 2020